Fablehaven : secrets of the dragon sanctuary / 4. - Mull, Brandon, 1974- (Mull, Brandon, 1974- Fablehaven., 2009)
When Kendra and Seth go to stay at their grandparents' estate, they discover that it is a sanctuary for magical creatures and that a battle between good and evil is looming.